Calculeaza (4/9)^10×[(27/8)^3]^2+(1/7)^0
Răspunsuri la întrebare
Răspuns de
1
(4/9)^10 × [(27/8)^3]^2 + (1/7)^0 =
= [(2/3)^2]^10 × {[(3/2)^3]^3}^2 + 1 =
= (2/3)^20 × (3/2)^18 + 1 =
= 2^20/3^20 × 3^18/2^18 + 1 =
= 2^2/3^2 + 1 =
= 4/9 + 1 =
= 4/9 + 9/9 =
= 13/9
Răspuns de
0
Răspuns:
13/9
Explicație pas cu pas:
(2/3)^20×[(3/2)^9]^2+1=(2/3)^18×(2/3)²×(3/2)^18+1=4/9+1=13/9
Alte întrebări interesante
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Chimie,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă